“ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AUDITOR SWITCHING SECARA VOLUNTARY PADA PERRUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2013-2015” - Latifa Rahmawati, 14.05.52.0130 (Students' Journal of Accounting and Banking, 2018)
The purpose of this study is to analyze the effect of percentage of ROA change, financial distress, KAP size and public ownership of auditors switching at manufacturing companies listed on Indonesia Stock Exchange (IDX). This research uses purposive sampling method in sample selection with sample criteria is manufacturing company listed on BEI during period 2013-2015. Based on these criteria obtained sample of 198 companies during 3 years of observation period. The relationship and / or influence between variables is explained using logistic regression analysis method. The results showed that percentage changes in ROA and financial distress has significant effect on the auditor switching. Variabels KAP’s size, klien’s size and public ownership has insignificant effect on the auditor switching.Keywords: Auditors Switching, Change Percentage ROA, Financial Distress, KAP’s Size, Klien’s Size and Public Ownership